2010
DOI: 10.3346/jkms.2010.25.6.841
|View full text |Cite
|
Sign up to set email alerts
|

High Transcript Level of FLT3 Associated with High Risk of Relapse in Pediatric Acute Myeloid Leukemia

Abstract: Identification of prognostic factors and risk-based post-remission therapy was proposed to improve the outcomes of acute myeloid leukemia (AML) and a mutation of FLT3 has been reported to be a risk factor, especially for pediatric patients. Recently, FLT3 expression level was implicated to have prognostic significance in adults, but little is known for childhood AML. To define the prognostic significance, transcript level of FLT3 was analyzed in 52 pediatric AML patients. The median copy number of FLT3 was 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…reported high FLT3 transcript level to be a poor prognostic factor in pediatric patients, but this study included only 5 patients in the highest FLT3 transcript expression level group. (39) Our results with CD135 MFI are in agreement with those from Kuchenbauer et al ., which showed that FLT3 transcript levels do not significantly affect OS or EFS, however they did observe a trend towards lower survival in the subset of FLT3 /WT patients with high FLT3 expression, which we did not observe with CD135 expression as determined by MFI. (28) It is important to note that in a smaller subset of patients with mRNA FLT3 transcript expression we did observe among FLT3 /ITD-negative patients a significantly lower EFS and corresponding increased RR, although there was no difference in OS.…”
Section: Discussionsupporting
confidence: 93%
“…reported high FLT3 transcript level to be a poor prognostic factor in pediatric patients, but this study included only 5 patients in the highest FLT3 transcript expression level group. (39) Our results with CD135 MFI are in agreement with those from Kuchenbauer et al ., which showed that FLT3 transcript levels do not significantly affect OS or EFS, however they did observe a trend towards lower survival in the subset of FLT3 /WT patients with high FLT3 expression, which we did not observe with CD135 expression as determined by MFI. (28) It is important to note that in a smaller subset of patients with mRNA FLT3 transcript expression we did observe among FLT3 /ITD-negative patients a significantly lower EFS and corresponding increased RR, although there was no difference in OS.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, high expression of wt FLT3 has been suggested to be associated with both distinct AML subtypes and an unfavorable prognosis in both adult and pediatric AML. [8][9][10] Mutations in the nucleophosmin gene (NPM1, 5q35) and in the CCAAT/enhancer binding protein, ␣ gene (CEBPA, 19q13) have been identified in patients with AML. 11,12 AML with mutated NPM1 or mutated CEBPA is associated with a favorable prognosis, [13][14][15][16] and these have been defined as provisionally distinct entities in the 2008 World Health Organization classification of AML.…”
Section: Introductionmentioning
confidence: 99%
“…Many clinical features such as favorable cytogenetics (eg, t[15;17], inv[16], and t[8;21] [1–3]) and a good initial treatment response are associated with a good outcome 4. However, the diagnosis encompasses a very heterogeneous group of leukemias with distinct response to chemotherapy 5. The clinical outcome of pediatric AML patients with similar treatment response varies greatly.…”
Section: Introductionmentioning
confidence: 99%